The Students’ Perceptions of the Strategies in the Process Approach - Eliwarti; Maarof, Nooreiny (Prodi Administrasi Pendidikan Program Pascasarjana Universitas Riau, 2017)
The main objective of this study was to examine the students’ perceptions of the strategies in the Process Approach. The subjects were 30 English Department students of Riau University taught using Process Approach. A set of questionnaire and semi-structured interview were used to collect the data. The level of perceptions was differentiated into three: Highly Positive, Positive and Negative. The results showed that all students had Positive and Highly Positive level of perception and no students had Negative perception of the strategies in the Process Approach. From the results of the interview, five categories were found. All of them reported positive opinions on the Process Approach and considered the editing and revising strategies as most useful. Besides, they stated that the steps in Process Approach were more systematic, specific, comfortable, more meaningful and livelier than other approaches. They all perceived that their writing performance had improved after the Process Approach intervention. The area of improvements were in collecting ideas, editing strategy, choice of words and the way how to write an essay. They also suggested on the application of the Process Approach for other writing classes. The findings from the interviews were in line with the findings from the questionnaire which revealed that students had favorable perceptions of the Process Approach. In light of these findings, it can be suggested that the Process Approach has the potential to be used as alternative instructional tools to improve students’ writing performance.